2005
DOI: 10.1890/05-0067
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a General Species–time–area Relationship

Abstract: The species-area relationship (SAR) plays a central role in biodiversity research, and recent work has increased awareness of its temporal analog, the species-time relationship (STR). Here we provide evidence for a general species-time-area-relationship (STAR), in which species number is a function of the area and time span of sampling, as well as their interaction. For eight assemblages ranging from lake zooplankton to desert rodents, this model outperformed a sampling-based model and two simpler models in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
264
6
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(293 citation statements)
references
References 27 publications
16
264
6
3
Order By: Relevance
“…Therefore, if fitted surfaces are only discussed inside the observed ranges then we may also consider models or parameter values that have the ability to produce unrealistic shapes (or results). Thus, both Adler et al (2005) and Storch et al (2005) have reported negative interaction terms (when applying model (7)). …”
Section: Adding An Interaction Termmentioning
confidence: 98%
See 4 more Smart Citations
“…Therefore, if fitted surfaces are only discussed inside the observed ranges then we may also consider models or parameter values that have the ability to produce unrealistic shapes (or results). Thus, both Adler et al (2005) and Storch et al (2005) have reported negative interaction terms (when applying model (7)). …”
Section: Adding An Interaction Termmentioning
confidence: 98%
“…Adler & Lauenroth (2003) and Adler et al (2005) have assessed the latter as a possible model for speciestime-area relationship (STAR). One often employs a logtransformation to improve the fit.…”
Section: Trivariate Modelsmentioning
confidence: 99%
See 3 more Smart Citations